2019
DOI: 10.1357/002224019828474241
|View full text |Cite
|
Sign up to set email alerts
|

The ecological and biogeochemical state of the North Pacific Subtropical Gyre is linked to sea surface height

Abstract: Sea surface height (SSH) is routinely measured from satellites and used to infer ocean currents, including eddies, that affect the distribution of organisms and substances in the ocean. SSH not only reflects the dynamics of the surface layer, but also is sensitive to the fluctuations of the main pycnocline; thus it is linked to events of nutrient upwelling. Beyond episodic upwelling events, it is not clear if and how SSH is linked to broader changes in the biogeochemical state of marine ecosystems. Our analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
93
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(113 citation statements)
references
References 0 publications
20
93
0
Order By: Relevance
“…The sampled eddies were generated in the central gyre away from continental margins, and the water masses inside and outside the eddies were in a similar distribution pattern. It indicates that eddy trapping anomalous waters is probably not predominant in these eddies, which is consistent with the results of Barone et al (2019). Plausible mechanisms for the enhancement of SCM in CEs are eddy pumping and diapycnal mixing.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The sampled eddies were generated in the central gyre away from continental margins, and the water masses inside and outside the eddies were in a similar distribution pattern. It indicates that eddy trapping anomalous waters is probably not predominant in these eddies, which is consistent with the results of Barone et al (2019). Plausible mechanisms for the enhancement of SCM in CEs are eddy pumping and diapycnal mixing.…”
Section: Discussionsupporting
confidence: 92%
“…Eddy pumping during the intensification of CEs could uplift isopycnals, upwell nutrients, and stimulate biological activity (Barone et al, 2019; Nicholson et al, 2008). While the eddy is in a relatively stable stage, diapycnal mixing is likely to facilitate upward nutrient supply in the core of CEs (Barone et al, 2019). At this stage, further upwelling of nutrients can still occur while the eddy translates if the eddy is a horizontally leaky system as proposed by Nencioli et al (2008).…”
Section: Discussionmentioning
confidence: 99%
“…Our analyses confirmed that symbiotic nitrogen-fixing cyanobacteria and their rhizosolenid diatom hosts are associated with SEP events, but also indicated that the free-living nitrogen-fixing cyanobacterium Crocosphaera ( 53 56 ) was also enriched on particles reaching the abyss during the SEP. In addition to diatom–diazotroph associations and free-living diazotrophic cyanobacterial groups, a wide variety of phototrophic and heterotrophic protists also appear to be key players in SEP events ( Fig.…”
Section: Discussionsupporting
confidence: 69%
“…3 28 . It may be that deep producers are sometimes uplifted into the upper 100 m of the euphotic zone during seasonal mixing events or ephemeral upwelling events like cyclonic mesoscale eddies 29,30 .…”
Section: The Abundance Of Phosphonate Producing and Consuming Microbementioning
confidence: 99%
“…Below 100 m, the genetic potential for phosphonate production shifts to other groups including SAR86, SAR11 IIb, the OM1 clade, MGI Archaea and the ZD0417 clade 28 . It may be that deep producers are sometimes uplifted into the upper 100 m of the euphotic zone during seasonal mixing events or ephemeral upwelling events like cyclonic mesoscale eddies 29,30 .…”
Section: Main Textmentioning
confidence: 99%